Bank Recycling of Petro Dollars to Emerging Market Economies During the Current Oil Price Boom - Wiegand, Johannes (Washington, D.C. : International Monetary Fund, 2008)
High oil prices have once again led to large external surpluses of oil exporting countries, similar to the 1970s and 1980s. This paper analyzes the extent to which (i) oil exporters use bank deposits to invest these surpluses, and (ii) banks are lending on these funds to emerging market economies. Bank recycling of petro dollars to emerging market economies is found to be almost as important as in the 1970s and 1980s, even though during the current boom, petro dollar bank flows tend to originate in countries like Russia, Libya, or Nigeria rather than in the Middle East. As one consequence, a fall in oil prices could yet again disrupt financing flows to emerging economies. Especially at risk could be countries that rely heavily on bank loans to finance external deficits, many of them in Emerging Europe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet